KAJIAN KELENGKAPAN RESEP PEDIATRI RAWAT JALAN YANG BERPOTENSI MENIMBULKAN MEDICATION ERROR DI RUMAH SAKIT SWASTA DI KABUPATEN GIANYAR - Piliarta, I Nyoman Gede; Swastini, Dewa Ayu; Noviyani, Rini (Jurnal Farmasi Udayana; Vol. 1, No. 1, Tahun 2012, 2013)
Pediatric prescribing need to get special attention  because drug utilization for pediatric is related with different rate of the development of the organ, body system, as well as enzyme that responsible to drug metabolism and drug excretion are not  complete yet. Medication error perhaps will be found in pediatric prescribing so a study about prescription that potentially made medication error happened must be carried out, therefore the medication error occurrence can be minimized or preventable. This study was run by using descriptive evaluative method by observing the prescription of some children in hospital at Gianyar regency during February to April 2009. The sample was conducted by accidental sampling. The total of prescriptions that used to be sample was 96. The data’s including: the age of patient, the variant of the drugs, dosages, and the type of drugs, so medication error could be observed or not. The Result of study showed that the total of male patients were 60,42% and female patients were 39,58%, while the age range of patients showed were between 6-11 months. There were 16 categories of drugs that used most frequent were cough and cold medicine about 20%, vitamin and mineral about 18,93%, and analgesic and antipyretic13,93%. The prevalence of error occured was 277 error that consist of 78,70% in pharmaceutical adjustment, 16,61% in clinical concideration, and 4,69 % in administration.
Keywords: medication error, pediatric, prescription